Теоремы о больших уклонениях в задаче проверки двух простых гипотез - Линьков, Ю.Н.; Медведева, М.И. (Український математичний журнал, 1995)
Доведено граничні теореми про великі відхилення логарифма відношення правдоподібності у задачі розрізнення двох простих гіпотез у загальній схемі статистичних експериментів з нульовою гіпотезою та з альтернативою, які застосовуються для дослідження спадання ймовірностей помилок 1-го та 2-го роду критерію Неймана - Пірсона. Limit theorems on large deviations of the logarithm of the likelihood ratio are proved for the problem of distinguishing two simple hypotheses in the general scheme of statistical experiments under the null hypothesis and under an alternative hypothesis. The theorems obtained are applied to the investigation of a decrease in the probability of errors of the first and second kind for the Neumann-Pearson criterion.